Comparison Analysis of Native Database Design with Object Oriented Design - Muhamad Fernandy; Khevien Rizkhi Darmawan; Daniel Yeri Kristiyanto (Research Group of Data Engineering, Faculty of Informatics, 2023)
Database design requires a structured database design, because the database contains data or information. The design method of the database design determines the structure of the designed design. Database design have two methods, either native or object-oriented method. Native database design has two stages, it is Data Flow Dia-gram and Entity Relationship Diagram, where as if it is object-oriented design using use case diagrams. It is ac-companied by class diagrams. Native designs tend to be more unstructured than object-oriented design. Native design focuses more on entity flow while object-oriented design focuses on database design entities. Another ad-vantage of using object-oriented design is the ease of explaining the database design to the client because of the simple design so that it can be easily understood. The method used in this research is prototype and relational algebra. The prototyping method is a technique to collect certain information about the user's information needs appropriately. This research focuses on comparing the native and object-oriented design.